إدارة المخاطر المالية ودورها في التنبؤ بالفشل المالي باستخدام نموذج Sherrod للبنك الوطني الجزائري( 2016- 2019) - غربي, خليل; جبار, محفوظ (جامعة الوادي - University of Eloued, 2022)
This study aims to show the extent of predicting the financial risk management, to avoid the financial failure of the National Bank of Algeria through the period (2016-2019), by relying on Sherrod's model that predicts borrowing risks and setting up a complete management for financial risk management that mandates early detection of the financialrisks keep up with these loans, to achieve this goal we relied on digital actual data extracted from the records and financial statements of the National Bank of Algeria. The study reached a set of results, The most important of which is that the National Bank of Algeria faces an glitchin in its financial indicators from year to year, we find that the model haspredicted financial failure because the z-values calculated during the study showes that they are medium-risk loans, as they are a critical area, and risk management must be activated to predict financial failure and address its causes.
management of the financial Risks and its role in forecasting financial failure using Sherrod's model Algerian National Bank( 2016- 2019)
مقال
Keywords: دارة المخاطر المالية؛ تنبؤ؛ فشل المالي; Sherrod.: management of the financial Risks ; forecasting ; financial failure